Internet of Things-Based Bus and Student Monitoring System on Free School Transportation Madiun City - Rosyadi, Arfian Dwiki; Puspaningrum, Lintang Diah; Hakimi, Musawer (Digitus : Journal of Computer Science Applications, 2024)
Traffic incidents and violations, particularly among students, pose safety concerns for parents and authorities. To address this issue, the Madiun City Government introduced the Free School Transport program through the Madiun City Transportation Office, providing school buses for students in Madiun City. However, despite this initiative, students and parents face challenges tracking bus arrivals due to weather conditions, traffic congestion, and schedule delays. This study proposes developing MASBUS, an Internet of Things (IoT)-based monitoring system for real-time school bus tracking. The system integrates a GPS module for location tracking and an RFID module for student identification. Data is transmitted via NodeMCU ESP8266 to a web server, stored in a MySQL database, and accessed through an Android application. The MASBUS app provides real-time location updates and sends automatic notifications when students board or leave the bus. The implementation of this system enhances student safety, improves transportation efficiency, and enables real-time monitoring for parents and school authorities. MASBUS contributes to a smarter and safer school transportation system by offering a more transparent and reliable tracking solution.